CUTANEOUS LUPUS ERYTHEMATOSUS - CLINICALPATHOLOGICAL CORRELATION OF LUPUS-SPECIFIC SKIN LESIONS - Pedrosa, Ana (2015)
Background: Lupus Erythematosus (LE) represents a multiorganic, autoimmune disease that affects mainly women of child-bearing age. The skin is the second most frequently affected organ, after the joints, and may precede the clinical onset of systemic symptoms.Objectives: To present the clinical findings which evoke the possibility of LE-specific skin lesions and the histopathological findings that may co-substantiate the diagnosis.Methods: Case studies of LE-specific skin lesions, in which the clinical-pathological correlation enabled the diagnosis of different subtypes of LE.Results: The correlation of clinical and histopathological findings, in a consistent serological setting, enabled the recognition of actual cases of LE-specific skin lesions: 1) acute; 2) subacute (annular and papulosquamous forms); 2.1) drug-induced subacute LE; 3) chronic, namely 3.1) classic discoid (face and scalp); 3.2) tumidus; 3.3) panniculitis.Moreover, the clinical and histopathological findings expected in other LE-specific skin lesions are described.Conclusions: Lupus Erythematosus exhibits a variability of cutaneous manifestations. The histopathology is critical for the diagnosis requiring a correct preservation and handling of biopsy material. Direct immunofluorescence remains useful to improve the diagnostic specificity. The accurate diagnosis, based in a systematic clinical-pathological correlation and integrated with the clinical and serological status, is crucial for the prognosis and treatment of the patients.